Do energy security and environmental quality contribute to renewable energy? The role of trade openness and energy use in North African countries. (December 2021) - Ibrahiem, Dalia M.; Hanafy, Shaimaa A.
Abstract: No considerable evidence is available in literature review regarding the drivers of renewable energy in North African countries. We attempt to fill this gap by empirically exploring the relationships among consumption of renewable energy sources, carbon dioxide emissions, economic growth, energy security, energy use, trade openness, foreign direct investment and population in North African countries mainly Egypt, Morocco and Tunisia from 1971 to 2014. To attain this objective, we use Panel PMG ARDL and Granger causality approaches to examine the co-integration and causality. Findings reveal that economic growth, emissions of carbon dioxide, trade openness and foreign direct investment trigger renewable energy which stress why policymakers can no longer overlook these variables while designing policies aiming at accelerating the shift towards renewable energy. On the contrary, energy security, energy use and population hamper it. Moreover, bi-directional causal relation between energy security and economic progress exists and energy security, direct foreign investments and deterioration in the environment cause renewable energy. In the light of these findings crucial policy implications concerning enhancing renewable energy technologies, encouraging green investment and promoting energy efficiency can be proposed.